Integrated Approach to Organisation of In-Service Training of Professionals Intended to Work for Public Governmental Bodies - IVO SVOBODA; ALEKSANDRIUK, TETIANA; DULIK, TETIANA; KLYMENKO, ANASTASIIA; RUDIANYN, IVAN (The journal of contemporary issues in business and government, 2020)
The purpose of the study was to identify how the integrated approach to the organisation of in-service training relied on an English language-based simulation team project simulation team project entitled “Build a Fair and Just State of 1000 people” influences the professional and personal qualities of the civil servants, and how the sampled individuals perceive the intervention. The study utilized quantitative and qualitative methods to establish the cause- effect relationships that had occurred in the variables due to the integrated approach used to organise the in-service training of the civil servants. The course participants’ professional efficacy, motivation, decision-making were the variables for the study. Five commonly used online psychometric tests for the civil servants were the instruments to measure the variables before and after the treatment. The project seen as the integrated approach to organising the course of in- service training of the civil servants brought positive changes to the participants’ professional efficacy, motivation, and decision-making. The sampled students acknowledged the effectiveness of this educational intervention and expressed satisfaction with its content, delivery mode, and the experience they gained from it. This study addressed the loopholes in the in-service training system of the civil servants such as succeeding in English language fluency and specific managerial skills and demonstrating certain beliefs, values, and behaviour patterns which were mentioned in the above document as the issues of reforming the training system of civil servants in Ukraine. The study implies that simulation games are an effective approach in training civil servants because they help them absorb professional knowledge through solving job-specific tasks. It also seems suggestive that the training system could be more decentralised, function- through-context-based with an assessment system that is flexible and situational based more on the practical than the theoretical component.